2019
DOI: 10.2147/cmar.s210825
|View full text |Cite
|
Sign up to set email alerts
|

<p>Role of Hippo/YAP signaling in irradiation-induced glioma cell apoptosis</p>

Abstract: Background: Although Hippo/Yes-associated protein (YAP) signaling plays crucial roles in radiation sensitivity and resistance of multiple kinds of cancers, its role in the radiation sensitivity of glioma cells remains unclear. The present study aimed to reveal Hippo/YAP role in the radiation sensitivity of glioma cells. Methods: Glioma U251 cells were administrated with different doses of irradiation. Cell Counting Kit-8 (CCK-8) and flow cytometry assays were used to assess cell viability and apoptosis. Co-imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Several studies have reported that high levels of YAP predict a poor response to RT. YAP activation induces resistance to radiation, while silencing YAP increases sensitivity to RT and potentiates the DNA damage response [ 215 , 216 , 217 ]. Genetic YAP inhibition or treatment with VP sensitizes triple-negative breast cancer cells to RT by targeting the DNA damage response and cell survival pathways [ 218 ].…”
Section: Biochemistry and Translational Properties Of Currently Known Yap Inhibitorsmentioning
confidence: 99%
“…Several studies have reported that high levels of YAP predict a poor response to RT. YAP activation induces resistance to radiation, while silencing YAP increases sensitivity to RT and potentiates the DNA damage response [ 215 , 216 , 217 ]. Genetic YAP inhibition or treatment with VP sensitizes triple-negative breast cancer cells to RT by targeting the DNA damage response and cell survival pathways [ 218 ].…”
Section: Biochemistry and Translational Properties Of Currently Known Yap Inhibitorsmentioning
confidence: 99%
“…In a glioma U251 cell line, irradiation induced cell apoptosis through high expression of c-caspase 3, caspase 3, and Bax. Irradiation also promoted a low expression of YAP and the inactivation of Hippo/YAP signaling through the ubiquitination mediated by RCHY1 ubiquitin ligase, as well as the high expression of Mst1, LATS1, MOB1, and SAVI ( 77 ). Whereas the medulloblastoma cells were irradiated, a YAP high expression was detected, which induced the cell proliferation through high-rise Cyclin D2 (CCND2), and phosphorylated H3 promoted the tumor aggressiveness and tumor recurrence.…”
Section: Tumor Cells Activate Signaling Pathways Involved In Dna-damage Response To Survive Ionizing Radiationmentioning
confidence: 99%
“…Hepatocyte necrosis and apoptosis occurs in HCV infection, and it is well documented that Yap downregulation is associated with enhanced apoptosis in normal and neoplastic cells. 65…”
Section: Hcv and Hippo Regulation Via Cd81mentioning
confidence: 99%